1998
DOI: 10.1042/cs0950269
|View full text |Cite
|
Sign up to set email alerts
|

Human cardiovascular variability, baroreflex and hormonal adaptations to a blood donation

Abstract: 1. We studied cardiovascular variability, baroreflex and blood volume regulating hormones to determine the relative roles of autonomic regulation and hormones during blood donation.2. The sympathetic response was studied by measuring the R-R interval and systolic blood pressure variability using coarse graining spectral analysis in eight blood donors. Beat-by-beat R-R intervals and blood pressure were recorded for 20 min before and 5 min after a whole-blood donation of 480+/-10 ml (about 7 ml/kg of blood volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…However, a recent study showed fluid replacement occurs rapidly, within the time range of the present study i. e. 6-7 min [12]. Alltogether, these compensatory mechanisms explain why a 10 % blood volume reduction does not markedly affect BP [5,9,28,32].…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…However, a recent study showed fluid replacement occurs rapidly, within the time range of the present study i. e. 6-7 min [12]. Alltogether, these compensatory mechanisms explain why a 10 % blood volume reduction does not markedly affect BP [5,9,28,32].…”
Section: Discussionsupporting
confidence: 50%
“…However, the present protocol of phlebotomy did not significantly increase HR and the cardiac output was consequently reduced. Similarly, Fortrat et al [5] did not observe any HR Fig. 1 Example from one patient of the effects of phlebotomy on the hemodynamic indices.…”
Section: Discussionmentioning
confidence: 82%
“…Nonetheless, whilst speculative, it is possible that after phlebotomy an increase in sympathetic activation due to moderate hypovolaemia (Fortrat et al . ; Zollei et al . ) may have masked a possible decrease in vascular resistance at peak exercise which would contribute as a peripheral adaptation to the increase in Q̇ peak and V̇O2 peak following ET (Klausen et al .…”
Section: Discussionmentioning
confidence: 98%
“…) related to the increase in sympathetic drive prompted by phlebotomy (Fortrat et al . ; Zollei et al . ).…”
Section: Discussionmentioning
confidence: 98%
“…Blood donation per se is not a stressful event and moderate stress, as suggested by increased cortisol levels and heart rate at the first donation, is secondary to emotional rather than to physical stimuli 12 . In determining the relative roles of autonomic regulation and hormones during blood donation, Fortrat et al 13 found that blood donation led to increases in the plasma catecholamines and an increase in systolic blood pressure. Heart rate, cardiovascular variability and the spontaneous baroreflex sensitivity did not change.…”
Section: Discussionmentioning
confidence: 99%